Factors Associated with Stress Levels in Self-Management of Type 2 Diabetes Mellitus Clients in Sempor Health Center Working Area 1: Faktor-Faktor yang Berhubungan dengan Tingkat Stres dalam Manajemen Diri Klien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Sempor 1 - Listiani, Andi; Sumarsih, Tri (Prosiding University Research Colloquium, 2024)
Background: The stress experienced by diabetes mellitus clients will have an impact on controlling blood sugar levels which, if not treated immediately, can trigger complications. Stress is a non-specific body response due to disturbed body needs which can be caused by internal or external factors, and if the stress level is high it can trigger an increase in blood sugar levels. This psychological impact can be reduced if the diabetes mellitus client’s self-management is carried out well. Research Objective: Analyze factors related to stress levels in self-management of type 2 diabetes mellitus clients in the Sempor Community Health Center Work Area 1. Research Method: This research is a quantitative descriptive study with a correlation research design using a cross-sectional approach. The sample in this research was 80 respondents and the technique used was purposive sampling. The research was carried out from June-July 2023. Stress levels were measured using the DASS 14 (Depression Anxiety Stress Scale) questionnaire (0.920), the DSMQ (Diabetes Self Management Questionnaire) questionnaire (0.934) and the diet compliance questionnaire (0.832). Data analysis used univariate analysis and bivariate analysis using the Chi Square test with a confidence value of 95%, namely ? = 0.05. Research Results:: The results of measuring the stress level of Type 2 DM clients carried out on 80 respondents, the majority of Type 2 DM clients experienced severe stress, 28 people (35.0%), the results of self-management measurements were 30 people (37.5%) had poor self-management, and the results of measuring diet compliance were 44 people (55%) who had a non-compliant diet. The results of the relationship between diet and stress levels obtained a p value of 0.005, the relationship between age and stress levels obtained a p value of 0.007, the relationship between education and stress levels obtained a p value of 0.046, the relationship between work and stress levels obtained a p value of 0.000, and the length of suffering from diabetes with stress levels. obtained a p value of 0.000. These results show that all the factors studied have a p value < 0.05, which means that all factors are interconnected with the level of stress in self-management of Type 2 DM clients in the Sempor 1 Community Health Center Work Area. Conclusion: There is a relationship between internal factors and the level of stress in self-management of Type 2 DM clients in the Sempor Community Health Center Work Area 1. Recommendation: it is hoped that future researchers can fulfill a sample of 100 respondents according to the provisions and can examine the stress level factors of Type 2 DM externally.